PENERAPAN METODE EKSTEMPORAN DAN MEDIA FLIPBOOK BERBICARA PADA PEMBELAJARAN MENCERITAKAN KEMBALI ISI DONGENG SISWA KELAS III - Regita Putri Yuniar; Panca Dewi Purwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of this study is to describe the application of the extemporaneous method and flipbook media in speaking, and to evaluate the effectiveness of the extemporaneous method and flipbook media in improving the storytelling skills of third-grade students at SDN 2 Wulung in Blora Regency. The research method used in this study is a mixed method with a sequential explanatory design. Data sources include both quantitative and qualitative data. Quantitative data collection techniques involve pretests and posttests, while qualitative data are gathered through student and teacher response questionnaires. The study concluded that the application of the extemporaneous method and flipbook media in teaching storytelling to third-grade students at SDN 2 Wulung in Blora Regency was well-implemented and effective. The effectiveness of the extemporaneous method and flipbook media, based on student learning outcomes, was normally distributed, and T-test calculations showed a significant difference between pretest and posttest results. The N-Gain test calculations indicated a moderate category. The study concluded that the application of the extemporaneous method and flipbook media can be well-implemented in teaching and is effective in improving the storytelling skills of third-grade students at SDN 2 Wulung in Blora Regency.